Oil Prices and the Kuwaiti and the Saudi Stock Markets - Azar, Samih Antoine; Basmajian, Loucine (International Journal of Economics and Financial Issues, 2013)
The purpose of this paper is to test the impact of oil price shocks on the stock markets of the two biggest and most liquid GCC equity markets, those of Kuwait and Saudi Arabia. It is expected that the two stock markets react similarly to oil price shocks. Actually the results show heterogeneity in responses. While there is prima facie evidence that both stock markets are influenced positively and linearly by oil price shocks, this evidence disappears when additional variables are added to the regressions. With the larger specification oil price shocks do not impact, neither linearly or non-linearly, Kuwaiti stock markets. By contrast Saudi markets react non-linearly to both oil price shocks and shocks in the US S&P 500. The only common feature for both equity markets is the positive relation with the shocks in the US S&P 500. Keywords: Oil prices; stock markets; Kuwait and Saudi Arabia; US S&P 500; GARCH; non linear relations JEL Classifications: G14; G15; F36; C22